Kebimbangan dan Kemerosotan Prestasi di Kalangan Atlet Lelaki di Peringkat Universiti - Ani Mazlina Dewi Mohamed; Mawarni Mohamed; Ruzli Zairazi; Mohd. Sofian Omar Fauzee (UiTM Publisher, 2007)
This research was conducted to further understand the relationship between anxiety and performance as indicated by Multidimensional Anxiety Theory. The main objective of this study is to identify as to how far cognitive and somatic anxiety influence the performance of male athletes in universities. It is hypothesized that there is a relationship between anxiety and performance. A total 125 male athletes between the age of 18-45 years old from a university that took part in the Malaysian Private Universities Games took part in this study. The data was collected using the Competitive State Anxiety Inventory-2 (CSAI-2) which was introduced by Martens, Vealey, Bump and Smith (1990). The respondents were asked to answer the questionnaire 30 minutes before the games began. The results of the study show that cognitive anxiety has a significant influence on performance while somatic anxiety is insignificant. The ANOVA test shows that there is no significant difference between cognitive anxiety and somatic anxiety among the university teams that took part in the Malaysian Private University Games.